Design and Analysis of Composite Biomaterial Bone Graft Plate - Hamdi, Dunia Abdulsahib; Khider, Fatima Mowafaq (Al-Nahrain Journal for Engineering Sciences, 2023)
The mixing technique was applied in this study to enhance the strength performance of the cement. The addition of 3% by weight of hydroxyapatite (HA) nanoparticles were mixed with 97% polymethyl methacrylate (PMMA) acrylic polymer, which has a nano size to serve as the matrix material. The surface roughness and continuous porosity of the bone cement were found to be slightly increased by the incorporation of nanoparticles, which enhanced bone-implant osseointegration and ingrowth. Atomic force microscopy (AFM) analysis revealed that the addition of hydroxyapatite (HAp) nanoparticles resulted in a surface roughness value (Sa) of 16.25 nm, which is similar to that of natural bone. The energy-dispersive X-ray spectroscopy (EDS) mapping results discover precentor material and uniform distribution. The Sample exhibited promising results in the antibacterial test, showing efficacy against bacteria both with and without sterilization, confirming its antibacterial properties. The mechanical tests conducted on the sample, including tensile, compression, bending and Vickers hardness tests, yielded favorable results and indicated that the sample is suitable for its intended application.  In the theoretical works the design of the bone, screw, and bone plate was conducted using SolidWorks, followed by an analysis using ANSYS under both axial and bending load conditions. The theoretical analysis revealed that the safety factor was less than 1 when an axial load of 13 N was applied and a bending load of 2 N was applied, indicating that the structure may not be able to withstand these loads safely. Under both ambient and physiologically relevant conditions in the human body, HA and PMMA have demonstrated to be excellent choices for enhancing the clinical performance of bone cement. This, in turn, can lead to increased longevity of implants, decreased patient risk, and lower healthcare costs